2021
DOI: 10.1590/acb360503
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of orthotopic renal transplantation. II. Size-matched porcine grafts in monkey recipients

Abstract: Purpose As a classical xenotransplantation model, porcine kidneys have been transplanted into the lower abdomen of non-human primates. However, we have improved upon this model by using size-matched grafting in the orthotopic position. The beneficial aspects and surgical details of our method are reported herein. Methods Donors were two newborn pigs (weighting 5 to 6 kg) and recipients were two cynomolgus monkeys (weighting, approximately, 7 kg). After bilateral nephrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For fetal kidney transplantation, we have shown that the periaortic region is superior for development in a small animal model of rats ( 23 ). In preclinical xenotransplantation of adult kidneys from pigs to monkeys, we have shown that orthotopic transplantation is superior ( 24 ). For the transplantation of renal organoids, we have previously developed a simple method of transplanting them under the renal membrane without damage ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…For fetal kidney transplantation, we have shown that the periaortic region is superior for development in a small animal model of rats ( 23 ). In preclinical xenotransplantation of adult kidneys from pigs to monkeys, we have shown that orthotopic transplantation is superior ( 24 ). For the transplantation of renal organoids, we have previously developed a simple method of transplanting them under the renal membrane without damage ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike tissue transplantation, the reaggregates are extremely fragile, and it was necessary to devise a transplantation method. In previous studies, we have reported the convenience of orthotopic transplantation 14 , 15 . The method we developed in the previous study was also selected for orthotopic transplantation under the renal capsule, but we established a method to detach the capsule, create a pocket space, and transplant the fragile organoids under water pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…Many other preclinical trials transplanting pig hearts, kidneys, islet cells, and cornea have been performed using effective immunosuppression regimens [27,63,[108][109][110][111][112]. Unfortunately, in these studies, PERV transmission was not analyzed, but at least no clinical signs of a retrovirus infection were observed.…”
Section: Rhesus Monkeysmentioning
confidence: 99%